The Effect of Giving Education with Power Point Leaflet Media and Isi Piningku Video on Increasing Knowledge of Balanced Nutrition in Students at SMP Negeri 7 Nabire Province Central Papua - Ithe Kogoya; Nur Susan Iriyanti Ibrahim; Gandhi Pratama (Lembaga Pengembangan Kinerja Dosen, 2024)
Nutritional problems in school children include malnutrition and overnutrition due to lack of education, so there needs to be education on the contents of my plate related to balanced nutrition. One of the program efforts that can be implemented by the government so that people live healthy and well-nourished is by providing education on the